2021
DOI: 10.4314/jsasa.v54i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing records management in municipalities with adverse audit opinions in Limpopo Province, South Africa

Abstract: This article assesses records management in municipalities with adverse audit opinions in the Limpopo province, South Africa. Audit reports issued by the Auditor-General of South Africa (AGSA) yearly indicate that poor recordkeeping is one of the factors contributing to adverse audit opinions in the public sector. The high level of corruption and maladministration, and lack of accountability and transparency in municipalities have become endemic and are a cause for concern in South Africa. Access to relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The private hospital further revealed that random visit to the offsite storage forms part of monitoring and evaluation plan to measure work progress. Marutha (2012) accentuated that it is vital to develop recurrent formal procedures for monitoring and auditing of electronic records systems. The author, however, did not describe the metrics that will guide the evaluation and tracking process.…”
Section: Journal Health and Technology -Jht Issn 2764-7625 Monitoring...mentioning
confidence: 99%
“…The private hospital further revealed that random visit to the offsite storage forms part of monitoring and evaluation plan to measure work progress. Marutha (2012) accentuated that it is vital to develop recurrent formal procedures for monitoring and auditing of electronic records systems. The author, however, did not describe the metrics that will guide the evaluation and tracking process.…”
Section: Journal Health and Technology -Jht Issn 2764-7625 Monitoring...mentioning
confidence: 99%
“…The overall problem is that, for many years, South Africa has been attempting to implement EHR systems in both public and private hospitals yet concerns and issues of managing change in the implementation have not been fully addressed. Even though several previous studies (Luthuli 2017, Marutha 2016, Thomas 2016, Katuu 2015, Marutha& Ngulube 2012, Weeks 2012) pointed out the necessity of implementing EHR systems to improve health service delivery in South Africa, the question regarding management of change has not been fully examined. There is no notable evidence regarding management of change in the KZN setting or specifically at Inkosi Albert Luthuli Central Hospital.…”
Section: Problem Statementmentioning
confidence: 99%
“…For example, Luthuli (2017), in a comparative analysis of public and private hospitals in KZN, acknowledged the need for ICT integration to improve management of health records for public health service delivery but did not examine change management in this integration process. Likewise, Marutha (2012) focused on the assessment of medical records management in healthcare service delivery in Limpopo Province and mentioned the need for adopting EHR systems to ensure successful delivery of health services, but the research falls short of recommending change management strategies in systems implementation. Thomas (2016) examined the EHR system implementation in primary healthcare and underscored the high degree of change that should be managed during pre-and post-adoption of the EHR systems.…”
Section: Problem Statementmentioning
confidence: 99%
“…According to Marutha and Ngulube (2012), due to a lack of effective record and payment management systems, health workers in both public and private institutions in most developing countries, particularly medical doctors and nurses, were either unable or struggling to provide timely and effective health services to citizens. In their view, ineffective record and payment management systems typically result in lengthy patient wait times before completing payment or getting health care.…”
Section: Introductionmentioning
confidence: 99%
“…computer hardware such as e-mails, database and word processing. It is an intangible soft record created and preserved through the usage of an ICT system (Marutha, & Ngulube, 2012). In the view of McDonald (2006), electronic records are the evidence, in digital form, of transactions undertaken by individuals or by organizations.…”
Section: Introductionmentioning
confidence: 99%